PENGGUNAAN MEDIA DALAM MENGINFORMASIKAN PROGRAM PEMBANGUNAN PADA HUMAS SEKRETARIAT DAERAH KOTA KENDARI - Nasrul , Laode Muh. Umran Marsia Sumule G (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
ABSTRACT The problem in this research is how to Use Media in Information Development Program at Public Relations Division of Regional Secretariat of Kendari City. The purpose of this study is to determine the use of media in the information development program at the Public Relations Division Regional Secretariat Kendari.The location of this research is conducted at the Mayor Office of Public Relations Sekerariat Daerah Kendari. The theory used is Uses and Gratification Theory by Katz and Blumer. In this study the number of informants as many as 5 people to represent the field of public relations Regional Secretariat Kendari. The type of data used in this study is the qualitative data and data analysis techniques used in this study qualitative descriptive analysis.The results of this study indicate that the role of Interpersonal Communication in improving the user's convenience in the Library and Filing Service of Southeast Sulawesi Province can not be separated from the Humanistic model and pragmatic model which shows that the quality of effective interpersonal communication is determined by five factors: openness, empathy ), Support (supportiveness), Positiveness (Positiveness), and Equality (equality). Of the five factors have not fully run perfectly in its main in terms of having a positive sense (positiveness).This research is expected to provide benefits and contributions of Science for Public Relations, especially Public Relations of the Regional Secretariat of Kendari. This study is also expected to provide benefits in the development of Communication Science, especially in the study of Media Use In Informing Program Development On Public Relations Regional Secretariat. Keywords: Interpersonal Communication, Librarian, Convenience